Discrepancy analysis in the prescriptions of patients admitted to the Surgical Center of a Public Emergency Hospital (Research, Society and Development, 2021)
Medication reconciliation has a strong impact on the prevention of adverse events and mistakes related to medications. The study aimed to observe the occurrence of divergences in the pharmacotherapy of surgical patients. Polymedicated patients were considered as those who used three or more medications. The sources used were the patient himself, his companion, the drugs taken at home taken to the hospital, and the consultation of the medical record. Discrepancies were considered as any unintentional change between the drugs used before admission and the drugs prescribed after the surgical intervention, which could be: omission of drugs, differentiation in doses, differences in frequency/time of administration, drug interaction, and therapeutic duplication. The collected data were tabulated and studied. During the work, 422 patients were admitted to post-surgical hospitalization. The main reason for admission was lower or upper limb amputation (41.3%); the average number of drugs used at home was 4.7. A total of 444 discrepancies were found and the average per patient was 5.5. The most relevant were interactions, equivalent to 53.4% ​​(n=237) of all identified discrepancies, then omission was 25.7% (n=114). Of the 106 interventions, only 15 were accepted. The discrepancies were found to indicate a high risk for the safety of these patients, requiring an effective process of recognition of home therapy when the individual is admitted to the hospital. Thus, measures to ensure patient safety at hospital admission and mitigate drug errors should be taken.